The effects of gemfibrozil on hyperlipidemia in children with persistent nephrotic syndrome - Büyükçelik, Mithat; Anarat, Ali; Karabay Bayazıt, Aysun; Noyan, Aytül; Özel, Ahmet; Anarat, Rüksan; Aydıngülü, Handan; Dikmen, Nurten (The Turkish Journal of Pediatrics, 2002)
Persistent nephrotic syndrome is frequently accompanied by severe hyperlipidemia, and this may pose a substantial risk for cardiovascular disease. Lipid-lowering drugs are prescribed by many nephrologists for adult patients but rarely for nephrotic children. The present investigation was designed to evaluate the safety and efficacy of gemfibrozil in nephrotic children. Eight girls and four boys aged from 5 to 17 years were enrolled in this study. They were all steroid and immunosuppressive resistant patients with nephrotic range proteinuria. Placebo was administered to five patients and gemfibrozil was administered to seven patients for four months. Blood samples were taken for the determination of cholesterol, triglyceride, low-density lipoprotein (LDL), high-density lipoprotein (HDL), BUN, serum creatinine (S_cr), ALT, AST, CPK, apolipoprotein A (apo A), apolipoprotein B (apo B), and serum albumin levels during the initial and subsequent examinations. At the end of the fourth month, gemfibrozil reduced total cholesterol by 34%, LDL by 30%, apo B by 21% and triglycerides by 53% (p < 0.05). HDL cholesterol and apo A levels were not significantly altered. Renal function and urine protein excretion were not affected by gemfibrozil. In this study gemfibrozil therapy had no side effects and had favorable effects on the lipoprotein profile of nephrotic patients.
Keywords: antilipid therapy; childhood; gemfibrozil; nephrotic syndrome